Educational, Developer and Educative Duties in the Taxonomy of Training Objectives - Sabina Hikmat, Alizade (2020)
Every person has ability of creative thinking. However, not every person can be called a creative person. Creative people are those who are smart and possess the ability to grasp realities and reactions to these realities. At the same time, people who achieve extraordinary inventions or realize creative acts can also be referred to as creative people. The creative way of thinking is the type of thinking resulting from inventing new things or improving other actions. The creative way of thinking is used to generate a large number of ideas. The main characteristic of the creative way of thinking as an intellectual system is the ability to analyze any problem, establish systematic relations, reveal contrasts, find out ideal solutions for these contrasts, and forecast possible versions for the development. The research carried out once more proved that the creative way of thinking is important for life. From this reason, the society that wants to achieve great successes and implement creative potential must try to make students improve their creative ways of thinking.